Development of a Cancer Vaccine Using In Vivo Click‐Chemistry‐Mediated Active Lymph Node Accumulation for Improved Immunotherapy. Issue 20 (31st March 2021) - Qin, Hao; Zhao, Ruifang; Qin, Yuting; Zhu, Jin; Chen, Long; Di, Chunzhi; Han, Xuexiang; Cheng, Keman; Zhang, Yinlong; Zhao, Ying; Shi, Jian; Anderson, Gregory J.; et al.
Abstract: Due to their ability to elicit a potent immune reaction with low systemic toxicity, cancer vaccines represent a promising strategy for treating tumors. Considerable effort has been directed toward improving the in vivo efficacy of cancer vaccines, with direct lymph node (LN) targeting being the most promising approach. Here, a click‐chemistry‐based active LN accumulation system (ALAS) is developed by surface modification of lymphatic endothelial cells with an azide group, which provide targets for dibenzocyclooctyne (DBCO)‐modified liposomes, to improve the delivery of encapsulated antigen and adjuvant to LNs. When loading with OVA257–264 peptide and poly(I:C), the formulation elicits an enhanced CD8 + T cell response in vivo, resulting in a much more efficient therapeutic effect and prolonged median survival of mice. Compared to treatment with DBCO‐conjugated liposomes (DL)‐Ag/Ad without the azide targeting, the percent survival of ALAS‐vaccine‐treated mice improves by 100% over 60 days. Altogether, the findings indicate that the novel ALAS approach is a powerful strategy to deliver vaccine components to LNs for enhanced antitumor immunity. Abstract : A click‐chemistry‐based active lymph node (LN) accumulation system is developed by surface modification of lymphatic endothelial cells with azide groups, which provide targets for dibenzocyclooctyne (DBCO)‐modified liposomes, to improve the delivery of encapsulated cargoes to LNs. When loading with antigens and adjuvants, the formulation elicits an enhanced immune response, resulting in a much more efficient therapeutic effect and prolonged survival of mice.